Bladder exstrophy in adulthood - R B Nerli; G V Kamat; S S Alur; Ashish Koura; Vikram Prabha; S S Amarkhed (Indian Journal of Urology, 2008)
Background: We report our experience with the treatment of classic exstrophy of the bladder in a small series of seven adult males. There are very few documented cases of adults presenting with exstrophy of bladder in literature. Materials and Methods: Adult males presenting with classic exstrophy of the bladder and complete epispadias underwent detailed evaluation including psychological assessment and counseling. All were explained regarding the surgical procedure and informed about the need for self-catheterization. Prior to 2002 all patients underwent cystectomy of the existing bladder plate, with creation of catheterizable modified Mainz pouch. Since 2002 patients were assessed for bladder reconstruction with augmentation ileocystoplasty, bladder neck reconstruction, and abdominal wall closure. Results: Seven adult males with classic exstrophy of the bladder and complete epispadias who had not received any previous treatment presented to us during the period 1991-2006. Five of these underwent cystectomy with continent pouch and the remaining two underwent bladder reconstruction. All have been doing well with improved self-esteem and social interaction. Two of these have married and leading a satisfactory sexual relationship. Conclusions: Surgical correction in adults with exstrophy of the bladder greatly improves self-esteem, confidence, and social relationship.